2016
DOI: 10.18240/ijo.2016.11.15
|View full text |Cite
|
Sign up to set email alerts
|

Missed retinal breaks in rhegmatogenous retinal detachment

Abstract: Pseudophakic patients, and patients with retinal bullae or advanced PVR should be carefully screened for MRBs. Though Weiss ring is a good indicator of PVD, it may still be over diagnosed in some cases. PVD is associated with retinal bullae and pseudophakia, and inversely with traumatic RRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Early detection of anterior retinal breaks is crucial because missed retinal breaks are responsible for up to 64% of the cases of failed RRD surgery [ 17 ]. Kornberg et al [ 15 ] also found that UWF imaging may be insufficient for detecting retinal breaks, especially in the far superior and inferior quadrants.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of anterior retinal breaks is crucial because missed retinal breaks are responsible for up to 64% of the cases of failed RRD surgery [ 17 ]. Kornberg et al [ 15 ] also found that UWF imaging may be insufficient for detecting retinal breaks, especially in the far superior and inferior quadrants.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this could be the presence of PVD in 138 (91%) of the patients, which is understandable given the age of the patients. Takkar et al reported a 50% prevalence of PVD in patients with RRD [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…IRB is a serious complication of VRS, and missing it can lead to failure of retinal surgery and vision loss. [ 6 ] The typically vulnerable cases include tractional retinal detachment without PVD and macular hole. The frequency of IRBs is close to 10% of the operated cases overall.…”
Section: Discussionmentioning
confidence: 99%